Membangun Data Desa Presisi di Desa Semplak Barat, Kabupaten Bogor - Ahmad Aulia Arsyad; Sofyan Sjaf; Rajib Gandi; Rama Maulana; I Made Prayoga Wijayanta; Reza Rama Gunada; Tri Ayu Alfiyasin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2021)
The Activity of Building Precision Village Data initiated by Dr. Sofyan Sjaf is an effort to serve the community, so that the village community can build, verify, and have accurate data regarding the condition of the village and its people as a basis for planning their village development. IPB as a university transfers knowledge in the form of data collection, verification, and analysis methods, as well as drone image-based mapping technology and the MERDESA census application to the village community. In this activity, IPB facilitates 1 lecturer, 2 alumni, and 4 IGTF students to work with the community to build Precision Village Data. Based on the data that has been collected, the people of Semplak Barat Village are quite potential to be the location of community service programs in the form of transfer of knowledge and technology, especially in the field of family-based yard land use, with commodities of fruit, vegetables or ornamental plants. The high use of the internet is also a potential channel that can be used for education and capacity building, especially during a pandemic which limits direct interaction between people inside and outside the village. IPB as a university which is very close to the village, needs to identify appropriate forms of development and community service programs based on Precision Village Data. Keywords: data, drones, IGTF, precision